Implementation of Community Empowerment Policy (Study on the Customary Institution of Haumeniana Village, Bikomi Nilulat Subdistrict, North Central Timor District, East Nusa Tenggara, Indonesia) - David Wilfrid Rihi; Ernawati Daeng; Rouwland Alberto Benyamin; Delila Anggelina Nahak Seran (Journal of Social Research, 2024)
Village customary institutions were formed with the hope of creating an understanding in building villages according to local values, but this goal cannot be realized according to the character of the local community and tends to exist traditional institutions only to fulfill the village government structure formally but do not have a role in the community empowerment planning process. The research is a descriptive research with a qualitative approach with information determined purposively with a total of 23 people, then the researcher will carry out the stages of data collection according to Creswell (2016:254-255) as qualitative observation, qualitative interview, search for qualitative documents) and qualitative audio and visual materials. The data that has been collected is then analyzed using data analysis techniques from Creswell (2016). The results of the study found that the implementation of community empowerment policies by the indigenous institutions of Haumeniana Village based on the policy implementation model from Donald Van Meter and Carl E. Van Horn (1975) found that; (1) policy standards have been flawed so that they tend to be bad policies that have been bad since the beginning, (2) human resources, incentives and infrastructure facilities are insufficient, (3) communication between organizations and strengthening activities are still ineffective, (4) the characteristics of implementing agents are constrained at the vertical level, (5) economic conditions in jurisdictions or implementing organizations are not enough to support policy implementation, (6) The disposition of the implementer is always ready to support the village government as a partner in empowering the community.